A role of non-FDG tracers in lung cancer? - Novruzov, Emil; Mori, Yuriko; Antke, Christina; Dabir, Mardjan; Schmitt, Dominik; Kratochwil, Clemens; Körber, Stefan A.; Haberkorn, Uwe; Giesel, Frederik L. (Seminars in nuclear medicine, 2022)
Since the introduction of PET/CT hybrid imaging about two decades ago the landscape of oncological imaging has fundamentally changed, opening a new era of molecular imaging with emphasis on functional characterization of biological processes such as metabolism, cellular proliferation, hypoxia, apoptosis, angiogenesis and immune response. The most commonly assessed functional hallmark of cancer is the increased metabolism in tumor cells due to well-known Warburg effect, because of which FDG has been the most employed radiotracer, the so-called pan-cancer agent, in oncological imaging. However, several limitations such as low specificity and low sensitivity for several histopathological forms of lung cancer as well as high background uptake in the normal tissue of FDG imaging lead to numerous serious pitfalls. This restricts its utilization and diagnostic value in lung cancer imaging, even though this is currently considered to be the method of choice in pulmonary cancer imaging. Accurate initial tumor staging and therapy response monitoring with respect to the TNM criteria plays a crucial role in therapy planning and management in patients with lung cancer. To this end, many efforts have been made for decades to develop novel PET radiopharmaceuticals with innovative approaches that go beyond the assessment of increased glycolytic activity alone. Radiopharmaceuticals targeting DNA synthesis, amino acid metabolism, angiogenesis, or hypoxia have been extensively studied, leading to the emergence of indications for specific clinical questions or as a complementary imaging tool alongside existing conventional or FDG imaging. Nevertheless, despite some initial encouraging results, these tracers couldn't gain a widespread use and acceptance in clinical routine. However, given its mechanism of action and some initial pilot studies regarding lung cancer imaging, FAPI has emerged as a very promising alternative tool that could provide superior or comparable diagnostic performance to FDG imaging in lung cancer entities. Thus, in this review article, we summarized the current PET radiopharmaceuticals, different imaging approaches and discussed the potential benefits and clinical applications of these agents in lung cancer imaging.